Application of Functionalized SWCNTs for Increase of Degradation Resistance of Acrylic Paint for Cars - Osiel Lucas Flores; Oxana V. Kharissova; Ubaldo Ortiz Méndez; Héctor Leija Gutiérrez; Edgar de Casas Ortiz; Boris I. Kharisov (Journal of Chemistry)
Physical properties of automotive acrylic paint are improved by incorporation of three different types of carbon nanotubes: single-wall carbon nanotubes (SWCNTs), OH-functionalized single-wall carbon nanotubes (OH-SWCNTs), and aniline-functionalized single-wall carbon nanotubes (aniline-SWCNTs). The formed composites are studied by electron miscroscopy methods and Raman spectrometry. It is found that the acrylic paints with addition of OH-SWCNTs and aniline-SWCNTs show better quality for their applications. In particular, the resistance against degradation by electron beam increased in ~500%.